Evolution of nitrogen functionalities in PAN-based carbon fiber during KOH activation to understand the formation of pore structure - Hlaine, Nang Kong Kham; Lee, Sora; Win, May Zaw; Yi, Kwang Bok; Kim, Kyoungsoo; Lee, Sungho (한국탄소학회, 2026)
Activated carbon fibers (ACFs) are highly efficient adsorbents for liquid and gaseous phases due to their tunable porosity, high surface area, and rapid adsorption kinetics. While polyacrylonitrile (PAN)-based ACFs are widely studied, the fundamental mechanisms governing nitrogen transformation and porosity evolution during chemical activation remain poorly understood. This study examines the structural, mechanical, chemical, and textural modifications in nitrogen-rich PAN-derived CFs during KOH activation, utilizing nitrogen contents and functionalities as indicators of the activation process. ACFs and crushed ACFs were prepared from pure PAN fibers by stabilization, carbonization, and KOH activation with different ratios at 600–900 °C. Aggressive activation conditions drastically reduced the nitrogen content and selectively decomposed specific nitrogen functionalities: pyridinic N diminished sharply, graphitic N remained comparatively stable, and pyrrolic N and pyridone species collapsed at higher temperatures. Structural and textural analyses revealed a correlation between increased disorder and lattice change, leading to the formation of a more uniform porous network in the crushed samples. However, this enhanced porosity came at the cost of mechanical integrity, as shown by reduced tensile strength and modulus. This study clarifies the relationship between activation parameters and the final properties of PAN-ACFs, providing a foundation for the optimized synthesis of these materials.